Taiwan's underwater cultural heritage documentation management - Y.-Y. Tung (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2015)
Taiwan is an important trading and maritime channels for many countries since ancient time. Numerous relics lie underwater due to weather, wars, and other factors. In the year of 2006, Bureau of Cultural Heritage (BOCH) entrusted the Underwater Archaeological Team of Academia Sinica to execute the underwater archaeological investigation projects. Currently, we verified 78 underwater targets, with 78 site of those had been recognized as shipwrecks sites. Up to date, there is a collection of 638 underwater objects from different underwater archaeological sites. Those artefacts are distributed to different institutions and museums. As very diverse management methods/systems are applied for every individual institution, underwater cultural heritage data such as survey, excavation report, research, etc. are poorly organized and disseminated for use. For better communication regarding to Taiwan’s underwater cultural heritage in every level, a universal format of documentation should be established. By comparing the existing checklist used in Taiwan with guidelines that are followed in other countries, a more intact and appropriate underwater cultural heritage condition documentation system can be established and adapted in Taiwan.